PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV SD NEGERI 005 LANGGINI BANGKINANG - Nurjannah, Nurjannah; Anggraini, Rini Dian; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research is a classroom action research aims to improve and eenhance the learning outcomes math. Implementation of the research done in class IV SDN 005 Langgini Bangkinang, were 20 students the second semester of 2012. The research was conducted by two cycles, each cycle performed three learning sessions and one tests. Quantitative data obtained through testing for learning outcomes and qualitative data about the activities of teachers and students through observation sheet. Quantitative analysis of the result of the analysis showed that the average score of the class IV SDN 005 Langgini has increased. Quantitative an increase in motivation, interests, and activities of students and teachers with type cooperative learning STAD. Based on the results of this study concluded that with the implementation of cooperative learning model type STAD can improve student learning outcomes math class IV SDN 005 Langgini.Key word: learning outcomes, learning cooperative type STAD.